Ο σκοπός της νύφης: το ταξίδι ενός κρητικού δημοτικού τραγουδιού στο χρόνο - Ζερβουδάκης, Δημοσθένης (2022)
The present diploma thesis is about a local folk song and its continuous impact on three consecutive generations. The information compiled indicates that the song was originally popular only with people in a certain region in Crete and it was closely connected with the traditions of the wedding ceremony. The island of Crete is a place where customs and traditions thrive, so different melodies where created in different parts of the island to accompany the bridal ceremony. Thus it is obvious that this melody did not establish its popularity nor did it become well known beyond this certain region as a custom. However, through years it was used in various styles to match different lyrics. Therefore today this folk song is performed in various ways as far as the genre is concerned. In fact, it is performed in places far beyond the island of Crete by remarkable well known artists in our country. It is very surprising however, that despite the great variety of the lyrics, in most cases they describe a feeling of separation.